Motivasi, Disiplin, Dan Semangat Kerja Dalam Meningkatkan Produktivitas Kerja Pada Masa Pandemi Covid-19 Di KPP Pratama Sidoarjo Utara - Savira Salsabillah Amalia; M Ridwan Basalamah; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to examine and analyze the variables that affect employee work productivity, consisting of motivation, discipline, and morale during the Covid-19 pandemic at KPP Pratama Sidoarjo Utara. This research is a type of quantitative research. The population in this study were 144 employees of KPP Pratama Sidoarjo Utara. The sample in this study amounted to 59 employees who were taken by simple random sampling technique. Methods of data collection using a questionnaire measured by a Likert scale and interviews with one of the employees. The analysis used is multiple linear regression analysis.From the research results it is explained that motivation, discipline, and morale have a simultaneous effect on work productivity with a smaller significance level. It can be seen that work productivity is significantly influenced jointly by discipline, motivation and morale. But partially, motivation has no effect on work productivity because motivation is also influenced by work environment factors and is not only influenced by yourself, this shows that the higher the level of employee motivation does not affect to increase employee work productivity while discipline and morale have an effect on productivity. work. Key words: Motivation, Discipline, Morale, and Work Productivity.